Influence of nonalcoholic steatohepatitis on the structural and functional conditions of the heart in patients with arterial hypertension, complicated by congestive heart failure - Вірстюк, Наталія Григорівна; Черкашина, Олена Євгенівна; Вакалюк, Ірина Ігорівна (ScienceRise: Medical Science, 2016)
At the present time nonalcoholic fatty liver disease is often regarded as one of the components of metabolic syndrome (MS), which may contribute to the development and progression of cardiovascular disease. The aim of the study was to investigate the influence of nonalcoholic steatohepatitis (NASH) on the structural and functional conditions of the heart in patients with arterial hypertension (AH) complicated by chronic heart failure (CHF). Methods. In 126 examinating patients with diagnosed and adjusted by medication AH complicated by CHF III-IV functional class NYHA indicators of the liver functional state and blood lipids were determined. Structural and functional conditions of the heart were assessed by echocardiography. Statistical analysis of the results was performed using "Statistica 10 Enterprise x64" ("Stat Soft", USA). Results. The presence of NASH was accompanied by violation of the liver functional state with moderate cytolytic and cholestatic syndromes and dyslipidemia in patients with AH complicated by CHF. A direct correlations between an atherogenic coefficient and activities of alaninaminotrasferase and hammahlutamiltranspeptydase in blood were revealed. It was found an adverse influence of NASH on the indicators of intra-cardiac hemodynamics and remodeling of the left ventricle (LV) to increase the thickness of the LV posterior wall, interventricular septum (IVS), myocardial mass and reduce the LV ejection fraction. Conclusions. The presence of NASH in patients with AH complicated by CHF adversely affect on structural and functional conditions of the heart and intra-cardiac hemodynamics and contributes to the progression of heart failure.